Caregiving Strain and All-Cause Mortality: Evidence From the REGARDS Study - Perkins, Martinique (Oxford University Press, 2013)
OBJECTIVES. Using a large, national sample, this study examined perceived caregiving strain and other caregiving factors in relation to all-cause mortality. METHOD. The REasons for Geographic and Racial Differences in Stroke (REGARDS) study is a population-based cohort of men and women aged 45 years and older. Approximately 12% (n = 3,710) reported that they were providing ongoing care to a family member with a chronic illness or disability. Proportional hazards models were used for this subsample to examine the effects of caregiving status measures on all-cause mortality over the subsequent 5-year period, both before and after covariate adjustment. RESULTS. Caregivers who reported high caregiving strain had significantly higher adjusted mortality rates than both no strain (hazard ratio [HR] = 1.55, p = .02) and some strain (HR = 1.83, p = .001) caregivers. The mortality effects of caregiving strain were not found to differ by race, sex, or the type of caregiving relationship (i.e., spouse, parent, child, sibling, and other). DISCUSSION. High perceived caregiving strain is associated with increased all-cause mortality after controlling for appropriate covariates. High caregiving strain constitutes a significant health concern and these caregivers should be targeted for appropriate interventions.